An Approach to the Notion of Situated Knowledge - Cerebello González, Emanuel; Chantré, Angélica; Orellana, Ernesto Erdmenger; Tosto, Virginia (Voices: A World Forum for Music Therapy, 2025)
The authors of this essay are members of the Knowledge Construction Commission of the Latin American Music Therapy Committee. In this paper, we set out to investigate the genealogy of the notion of situated knowledge. The notion arises from standpoint theory(Harding, Haraway) and has been fruitful in debates about ways of constructing knowledge that have taken place during the second half of the 20th century. In conjunction with critical geography, it has made it possible to question positivist assumptionsand to propose that: a) knowledge is constructed in particular social and historical conditions, affected by political processes; b) it follows that considering knowledge, including scientific knowledge, as universal, neutral, and objective is a myth; c) communities have epistemic privilege when it comes to accounting for their experiences and realities; and, d) the situated nature does not refer to geographical locations but to the reflective and critical processes carried out by communities. Editorial Comment In this short essay, the authors ask themselves what conditions are required for knowledge to be considered situated. Their reflections lead us to recognize the performative nature of the spaces in which we carry out our professional practices, develop theories, and conduct research. They raise situations of injustice due to cognitive capitalism but, at the same time and in line with decolonial perspectives, they assert their position of epistemic privilege to narrate the development of the discipline in the region.